Oocytes With Smooth Endoplasmic Reticulum Aggregates May Not Impact Blastocyst Euploidy Rate - Xu, Jian; Yang, Li; Chen, Zhi-Heng; Yin, Min-Na; Chen, Juan; Sun, Ling (Frontiers in Endocrinology, 2022)
Objective: To investigate whether the euploidy rate of blastocysts derived from smooth endoplasmic reticulum aggregates (SERa) positive cycles and oocytes are impacted. Design: Retrospective cohort study. Method(s): A total of 601 preimplantation genetic testing (PGT) cycles with at least one oocyte retrieved in our center between April 2017 and May 2021 were initially included in the study. Women＞35 years and PGT cycles with chromosomal structural rearrangements (PGT-SR) were excluded. Embryological and blastocyst ploidy outcomes were compared among SERa+ oocyte, sibling SERa- oocytes and oocytes in SERa- cycles. Results: No significant difference was observed among the SERa+ oocyte group, sibling SERa- oocyte group and SERa- cycle group in the normal fertilization rate (82.1 % vs. 77.8 % vs. 83.1 %, respectively, P=0.061), blastocyst formation rate (71.0 % vs. 72.5 % vs. 68.4 %, respectively, P=0.393), good quality blastocyst formation rate (46.4 % vs. 48.3 % vs. 42.6 %, respectively, P=0.198). No significant difference was observed in the euploidy rate (50.0 % vs. 62.5 % vs. 63.3 %, respectively, P=0.324), mosaic rate (12.5 % vs. 9.7 % vs. 13.4 %, respectively, P=0.506) and aneuploidy rate (37.5 % vs. 27.8% vs. 23.2 %, respectively, P=0.137) among the three groups. Conclusion: Our results suggest that the euploidy rate of blastocysts derived from SERa+ cycles and oocytes may not be impacted.